C‐reactive protein is essential for innate resistance to pneumococcal infection. Issue 3 (July 2014) - Paul Simons, J.; Loeffler, Jutta M.; Al‐Shawi, Raya; Ellmerich, Stephan; Hutchinson, Winston L.; Tennent, Glenys A.; Petrie, Aviva; Raynes, John G.; de Souza, J. Brian; Lawrence, Rachel A.; Read, Kevin D.; Pepys, Mark B.
Summary No deficiency of human C‐reactive protein (CRP), or even structural polymorphism of the protein, has yet been reported so its physiological role is not known. Here we show for the first time that CRP‐deficient mice are remarkably susceptible to Streptococcus pneumoniae infection and are protected by reconstitution with isolated pure human CRP, or by anti‐pneumococcal antibodies. Autologous mouse CRP is evidently essential for innate resistance to pneumococcal infection before antibodies are produced. Our findings are consistent with the significant association between clinical pneumococcal infection and non‐coding human CRP gene polymorphisms which affect CRP expression. Deficiency or loss of function variation in CRP may therefore be lethal at the first early‐life encounter with this ubiquitous virulent pathogen, explaining the invariant presence and structure of CRP in human adults.